Respuesta :

Answer:

Step-by-step explanation:

for side a

take 60 degree as reference angle

using tan rule

tan 60 =opposite /adjacent

[tex]\sqrt{3}[/tex] = a/6

do cross multiplication

6*[tex]\sqrt{3}[/tex] =a*1

[tex]6\sqrt{3} = a[/tex]

for b

using pythagoras theorem

a^2 + b^2 =c^2 (here a nd b are the legs of a right triangle and c is hypotenuse)

6^2 + [tex](6\sqrt{3})^2 = b^2[/tex]

36 + 6*6*3 = b^2

36 + 108 = b^2

144 = b^2

[tex]\sqrt{144}[/tex] = b

14 = b

for angle c

take 45 degree as reference angle

using cos rule

cos 45 = adjacent/hypotenuse

[tex]\frac{1}{\sqrt{2} } = \frac{c}{12}[/tex]

do cross multoplication

[tex]c*\sqrt{2} = 12*1[/tex]

[tex]c = \frac{12}{\sqrt{2} } \\\\c = 6\sqrt{2[/tex]